Eksplorasi Kebijakan dan Hukum Tentang Green Economy ditinjau dengan Islamic Legal Maxims di Indonesia - Kamaluddin, Imam; Setiawan, Bagus; Jakiyudin, Ahmad Havid (Universitas Serang Raya, 2023)
Based on Indonesian ideals of environmental concern, the green economy was started to transform economic development. The green economy is a spoke of sustainable development because of its revolutionary and transformative effects in the fields of economics, society, and the environment. Unintentionally, numerous laws and regulations include provisions related to the green economy. It is fascinating to analyze from the standpoint of Islamic legal maxims (fiqh rules or qawaid fiqhiyyah) in order to illuminate the significance and motivation behind the adoption of pertinent legal rules and policies. This study intends to investigate the substance of legal studies on the green economy in Indonesia before further analyzing it in light of Islamic legal principles. The research findings are interpreted using a normative juridical research technique. The study of positive law and the literature on Islamic law are sources of information. The study's findings indicate that there isn't a particular law that has provisions related to the green economy in terms of terminology. However, laws and government rules pertaining to environmental protection from an economic standpoint can be found that contain the substance. Therefore, in Presidential Decree No. 98/2021, the government more thoroughly regulates it. Government initiatives and laws pertaining to the green economy can be seen from the perspective of Islamic legal maxims as fulfilling fiqh norms. The current policy is a legal requirement that obliges the legal community to abide by it and contribute to the realization of a green economy. It represents the government's goal to eliminate the risks brought on by environmental degradation.